The role of performance analysis within the coaching process: Dealing with failure in volleyball side out attack - Degrenne, O.; Langlois, V.; Paulo, A.; Éloi, S.; Mouchet, A. (Movement & Sport Sciences - Science & Motricité, 2023)
Performance analysis has been a key-element in team sports such as volleyball for a long time, playing a role in the coaches` learning through the association of their lived coaching experience with objective data. A discriminant performance indicator on winning a volleyball set is the effectiveness of attack after reception - i.e., side out attack. So, it is important for coaches` future interventions to identify how expert setters deal with unsuccessful side out attacks. Thus, the aim of the present study was to analyze, in an elite level competitive context, the setter`s decision making after a failed side out attack. A total of 44 matches were analyzed from the 2014 and the 2018 Men`s World Championships and the 2016 Olympic Games. The sample included all lost side out sequences (SO1), followed by the subsequent side out play (SO2), which resulted in a final sample of 499 "side out" sequences. Results indicated that after a failed side out, using a faster attack tempo was the best way to win the rally, and that in more than half of the sample, setters inverse their setting from SO1 to SO2. Our findings are informative for volleyball coaching, specifically for setting practice, athlete development, in-game decision making and scouting.